Approaches to data analysis in visual education research - Cescato, Silvia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
This paper reviews the potential for analysing visual research data in the areas of education and training, in light of the increasing importance of the visual in contemporary life. The main challenges associated with the use of video tools in educational research are examined from both the theoretical and practical points of view. Key issues explored include problematising the researcher’s perspective, and identifying and selecting tools and methods of data analysis that are suited to the field of “visual pedagogy”. These aspects, especially that of how to approach the analysis of visual data, speak to key questions in educational research. It is argued that in a culture in which visual impact plays a key role (Lyotard, 1984), knowing how to “use visual data is a core competence” and that greater awareness of this methodological approach “can enhance quality in research” (Id., p. X) and training.